Assessment of two minimally invasive methodologies for sex identification in the European eel, Anguilla anguilla - Michael J. Williamson; Jack A. Brand; Kevin Hopkins; Luke O'Connor; Matthew W. Perkins; Christopher Sergeant; Simon Spiro; Taina Strike; Jessica Whinfield; Rosie S. Williams; Ethan Wrigglesworth; Rosalind M. Wright; et al. (Journal of Fish Biology, 2026)
Sex is an important driver of variation in behaviour, ecology and physiology. Sex identification in the Critically Endangered European eel ( Anguilla anguilla ) currently requires fish sacrifice, or the use of morphological differences such as body length, which can be inaccurate in certain habitats and at intermediate body lengths. Non‐lethal tools for accurate sex identification in this species are therefore required. Here, we test the efficacy of two minimally invasive methods of sex identification: (1) ultrasonography and (2) molecular markers taken from pectoral fin clips. Both methodologies were applied to riverine European silver eel and compared to histological sex identification. Ultrasonography accurately identified the gonads in female eel, with males identified by the absence of detectable gonadal structures. The level of expression of three molecular markers ( dcn, LOC111853410 , kera ) previously used to identify sex in Japanese eel ( Anguilla japonica ) were evaluated. There was no significant differential expression of the three molecular markers between sexes, suggesting that these markers cannot be accurately used to identify sex in European eel. Our findings suggest that minimally invasive imaging using ultrasonography can be a reliable tool for identifying sex in early‐stage adult migratory European eels, with particular use at intermediate sizes (400–500 mm) and animals in habitats where migration potential is limited and may regularly exceed typical growth sizes. This technique can be highly valuable for studies that address ecological, behavioural, conservation and management issues in this Critically Endangered species.

Entamoebiasis in zoological non-human primates in the United Kingdom - Daniela Denk; Rachel E. Taylor; Mark F. Stidworthy; Simon Spiro (Journal of Comparative Pathology, 2025)

Histopathological characterization and grading of chronic enterocolitis in Sulawesi crested macaques (Macaca nigra) - Yannick Van de Weyer; Mark R. Howard; Mark F. Stidworthy; Alberto R. Barbon; Julian Chantrey; Stamatios A. Tahas; Ethan Wrigglesworth; Lewis J. Rowden; Amanda Guthrie; Simon Spiro (Journal of Comparative Pathology, 2024)

Northerly range expansion and first confirmed records of the smalltooth sand tiger shark, Odontaspis ferox , in the United Kingdom and Ireland - David J. Curnick; Rob Deaville; Jenny R. Bortoluzzi; Luke Cameron; Jeanette E. L. Carlsson; Jens Carlsson; Haley R. Dolton; Cat A. Gordon; Phil Hosegood; Alicia Nilsson; Matthew W. Perkins; Kevin J. Purves; et al. (Journal of Fish Biology, 2023)
Three Odontaspis ferox (confirmed by mtDNA barcoding) were found in the English Channel and Celtic Sea in 2023 at Lepe, UK (50.7846, −1.3508), Kilmore Quay, Ireland (52.1714, −6.5937), and Lyme Bay, UK (50.6448, −2.9302). These are the first records of O. ferox in either country, and extend the species' range by over three degrees of latitude, to >52° N. They were ~275 (female), 433 (female), and 293 cm (male) total length, respectively. These continue a series of new records, possibly indicative of a climate change−induced shift in the species' range.